-2t-2=7t-14-7t

Simple and best practice solution for -2t-2=7t-14-7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2t-2=7t-14-7t equation:



-2t-2=7t-14-7t
We move all terms to the left:
-2t-2-(7t-14-7t)=0
We add all the numbers together, and all the variables
-2t-2-(-14)=0
We add all the numbers together, and all the variables
-2t+12=0
We move all terms containing t to the left, all other terms to the right
-2t=-12
t=-12/-2
t=+6

See similar equations:

| x/3=5/35 | | 7/4z=42 | | 24=4u+2u | | 16x-7x=81 | | x+3/8=-3 | | 2p+2=63 | | 0=(m+4)(m-4) | | -1+16n=10n-19 | | 7m-20m-10=3 | | (Y-0)=16(x-2) | | 4=z-11/4 | | 10m-2/5=9.60 | | 54+89+x/3=76 | | Y-0=16(x-2) | | 9x=-x+8 | | -13j-12=-12j | | -6t-5=-7t-11 | | 1/2x-2/3=3/4x+1/2 | | -15w=-16-7w | | -15w=-16–7w | | 37+2x=180 | | -16j=-18j+12 | | 54=(4x+6)(2x) | | t+11/2=-4 | | 6x^2-18x-98=0 | | 18n+-11n-18=-3 | | 20+7h=6h | | 3b+5=6b-3b+8-9 | | 5k-10=7k+8 | | -18=-3(h-9) | | (X+4)+3(5-2x)=11 | | 20-9k=-20+11k |

Equations solver categories